"Stay home?" the rhetoric of the right to housing in the context of the Covid-19 pandemic in Brazil (Ágora Journal, 2022)
This article aims to discuss the fundamental right to housing from the Covid-19 pandemic in Brazil. We parties from the recognition that, historically, housing policy is constituted as an instrument for maintaining privileges for capitalist accumulation, by promoting process for expropriation, which support the urban entrepreneurship. We try to demonstrate that this logical was pemanent during the crisis. To this end, we will seek analyze State intervention, which has based on a series of expropriations, which combine removals and unfunding of ongoing housing programs. It is not without struggles that these expropriations have been consolidated, given the resistance of urban social movements. This study integrates the reaserch of Programa de Estudos de América Latina e Caribe (PROEALC/UERJ).
Keywords: Pandemic; Expropriations; Housing politics